HIGH-YIELDING COWS PERFORMANCE AND ELEMENTS METABOLISM IN THE SECOND 100 DAYS OF LACTATION UNDER THE USING OF ZINC, MANGANESE AND COBALT MIXED LIGAND COMPLEXES - Kropyvka, Yu. G.; Bomko, V. S.; Babenko, S. P. (Scientific Progress & Innovations, 2021)
The study results indicate that the doses of mixed ligand complexes of Zinc, Manganese and Cobalt with the using of Suplex Selenium, Cuprum Sulfate and Potassium Iodide in the second 100 days of lactation had a positive effect on milk productivity. The average daily milk yields in cows of the experimental groups were 1.85 kg higher in group 2, and in the experimental groups 3, 4 and 5 the yields were higher by 2.72, 4.32, 5.53 kg, or 6.38, 9.37, 14.89 and 19.06 %, respectively, and the difference was reliable. The results of Zinc, Manganese and Cobalt metabolism also confirm higher average daily yields in the study groups. Thus, depo-sition of Zinc in the cows of the experimental groups 3, 4 and 5 were respectively by 59.6, 47, and 49.3 mg higher as compared with the control; and in comparison with the experimental group 2, in the cows of groups 3, 4 and 5, Zink deposition was by 6.6, 19.2 and 36.1 mg lower, respectively. However, in cows of the experimental groups 4 and 5 (the diets of which contained by 11 % and 22 % less of pure Zinc, Manganese and Cobalt as compared with the experimental group 3) less Zink was deposited by 12.6 and 10.3 mg, re-spectively, in comparison with the experimental group 3. The highest percentage of digested Zinc from con-sumed was in cows of the experimental groups 3, 4, and 5 – 56.8, 65.6, and 78.6 %, respectively, while in the control group 1 it was 40.1 %, and in the experimental group 2 it made 44.8 %. Concerning manganese deposition in the animals of the experimental groups 3, 4 and 5 it was significantly lower than in the control and the experimental groups 2. Manganese assimilation in the group 3 made 40.2 %, in the groups 4 and 5 it made 41.2 and 39.3 % of the consumed amount, respectively, while in the group 1 it made 19.9 %, and 36% in the group 2. In the animals, which consumed Cobalt in the form of mixed ligand complex (experimental groups 3, 4, 5), the trace element was assimilated by 52.5, 53.1, 60.1 %, respectively, whereas in the control group 1 – by 53.2 %, and in the experimental group 2 – by 50.4 %. The using of Zinc, Manganese and Co-balt mixed ligand complexes enhances milk productivity and reduces the need for these elements. The me-tabolism of Zinc, Manganese and Cobalt in the cows bodies is proven by the best results in the experimental group 5, in which 1 kg of dry matter in mixed feed contained 35 mg of Zinc, 35 mg of Manganese, 0.4 mg of Cobalt, 0.3 mg of Selenium, 10 mg of Cuprum, and 0.9 mg of Iodine.